Leadership Success System in Improving Education Quality at Madrasah Diniyah Takmiliyah Awaliyah - Daulay, Sakti; Zulfamanna, Zulfamanna; Ilham, Seprian (Ahlussunnah: Journal of Islamic Education, 2025)
This study was motivated by the researcher's interest in examining the leadership success system of Madrasah Diniyah Takmiliyah Awaliyah principals, particularly the leadership methods applied to improve the quality of education. The head of Madrasah Diniyah Takmiliyah Awaliyah is considered capable of bringing positive changes every year, improving the quality of education even though the facilities and infrastructure are not yet adequate, and becoming a role model for teachers and students. In addition, the head of Madrasah Diniyah Takmiliyah Awaliyah has an open attitude towards change by providing training to teachers and conducting comparative studies with other Madrasah Diniyah Takmiliyah Awaliyah. This condition is different from the two comparative Madrasah Diniyah Takmiliyah Awaliyah, which show weak leadership that has resulted in the stagnation and even demise of the institution. This study aims to determine the system of successful leadership of the head of Madrasah Diniyah Takmiliyah Awaliyah in improving the quality of education at Madrasah Diniyah Takmiliyah Awaliyah. This study uses a qualitative method with a field study approach. Data collection techniques were carried out through observation, interviews, and documentation, with instruments in the form of observation guidelines, interview guidelines, and documentation guidelines. Data analysis results were carried out through the stages of data reduction, data presentation, and data verification, while data validity was tested through source triangulation and method triangulation. The results of the study show that the leadership of Madrasah Diniyah Takmiliyah Awaliyah applies three main methods, namely uswatun hasanah, democracy, and transformational. The application of these methods has a positive impact on the moral character of students, increased participation of teachers, parents, and the community, as well as the development of teacher quality, enthusiasm for learning, and curiosity about new knowledge. The results of this study are expected to serve as a reference in the development of leadership at Madrasah Diniyah Takmiliyah Awaliyah to improve the quality of education.